Metabolomic and cytokine profiles of high-risk sepsis phenotypes in children - Ryan R. Hurtado; L. Nelson Sanchez-Pinto (Scientific Reports)
Abstract Children with sepsis are at risk of developing life-threatening multiple organ dysfunction (MODS). We have previously described two sepsis phenotypes associated with poor prognosis: “persistent hypoxemia, encephalopathy and shock” (PHES) and “sepsis-associated persistent MODS” (PMODS). We hypothesized there are unique metabolomic and cytokine profiles associated with these phenotypes that will allow for better identification and understanding of their pathophysiology. To test this, plasma samples from 50 children with sepsis-associated MODS were categorized as meeting criteria for PHES, PMODS or assigned as controls. Concentrations of 166 lipids, 26 metabolites and 20 cytokines were measured and analyzed. Of 50 patients, 17 were classified as the PHES phenotype and had upregulation of pro-inflammatory cytokines and an endothelial activation biomarker compared to controls (p < 0.05). 14 patients were classified as PMODS and had significant downregulation of immune mediators compared to controls (p < 0.05). Both phenotypes were associated with mitochondrial dysfunction based on the metabolic profiles of lysine, carnitine, and short and long chain fatty acids. Our results demonstrate metabolomic, immune, and endothelial dysregulation associated with two high-risk sepsis phenotypes in children. If validated, our findings suggest there may be several immune modulation, endothelial repair, and metabolic support therapies that could be tested in these phenotypes.